Urinary cyclic AMP in vitamin D deficiency rickets - Yordam, Nurşen; Ciliv, Gönenç; Saatçi, Ümit; Özsoylu, Şinasi (The Turkish Journal of Pediatrics, 1983)
In this study 28 children with vitamin D deficiency rickets and 11 control cases were studied. The rise in Cp as well as the fall in TRP % were strikingly different in the rickets patients as compared to the control cases. The Cp/Ccr ratio was considerably higher in the rickets patients than in the controls. The daily excretion of urinary cAMP was elevated 2.5-fold in patients with rickets and further, a negative correlation between the serum calcium levels and daily urinary excretion of cAMP was observed. The infusion of calcium decreased the urinary level of cAMP significantly both in control cases and in patients. The effect of vitamin D treatment was detected, the mean value in these cases being essentially the same as that of the controls. These data suggest that in man the result of vitamin D deficiency can be overcome by secondary hyperparathyroidism as a result of which an increased renal tubular formation of cAMP occurs.